Fragility analysis of structures incorporating control systems - Wilbee A.K. (2015)
This research is partially supported by National Science Foundation Grant No. 1148255. The second and third authors, respectively, acknowledge the support of the Department of Science, Technology, and Innovation - COLCIENCIAS and the Colombia-Purdue Institute for Advanced Scientific Research, as well a the National Council for Science, Technology and Technological Innovation - CONCYTEC, Peru. This support is gratefully acknowledged.